The Relationship Between Self Efficacy, Work Life Balance and Work Overload on Emotional Exhaustion of Students Who Work Part Time - Farhana Fauziah; Sri Seviandini; Sandi Nasrudin Wibowo (Indonesian Journal of Business Analytics, 2024)
University students are an intellectual group that is currently enrolled in classes. Students engage in employment and business off campus in addition to their coursework. In order to reduce emotional exhaustion in students who work part-time, this research aims to investigate the relationship between work overload, work-life balance, and self-efficacy. It is hoped that this research will serve as an assessment tool for employers, encouraging them to focus more on employee work-life balance, self-efficacy, and work-life balance. emotional weariness. The methodology used in this study is quantitative. Purposive sampling together with statistical techniques were used to properly assess the data. SmartPLS 3 software is used in this study to evaluate the theoretical framework. Combining assessments of discriminant and convergent validity allowed for the verification of construct validity. Internal consistency testing was used to assess construct reliability. The significance is evaluated using the bootstrapping technique. The study's findings indicate that the emotional tiredness experienced by students who work part-time is significantly influenced by job overload, work-life balance, and self-efficacy.